Effect of the Carbon Concentration, Blend Concentration, and Renewal Rate in the Growth Kinetic of Chlorella sp. - Adriano Arruda Henrard; Gabriel Martins da Rosa; Luiza Moraes; Michele Greque de Morais; Jorge Alberto Vieira Costa (The Scientific World Journal)
The microalgae cultivation can be used as alternative sources of food, in agriculture, residual water treatment, and biofuels production. Semicontinuous cultivation is little studied but is more cost-effective than the discontinuous (batch) cultivation. In the semicontinuous cultivation, the microalga is maintained in better concentration of nutrients and the photoinhibition by excessive cell is reduced. Thus, biomass productivity and biocompounds of interest, such as lipid productivity, may be higher than in batch cultivation. The objective of this study was to examine the influence of blend concentration, medium renewal rate, and concentration of sodium bicarbonate on the growth of Chlorella sp. during semicontinuous cultivation. The cultivation was carried out in Raceway type bioreactors of 6 L, for 40 d at 30°C, 41.6 µmol m−2 s−1, and a 12 h light/dark photoperiod. Maximum specific growth rate (0.149 d−1) and generating biomass (2.89 g L−1) were obtained when the blend concentration was 0.80 g L−1, the medium renewal rate was 40%, and NaHCO3 was 1.60 g L−1. The average productivity (0.091 g L−1 d−1) was achieved with 0.8 g L−1 of blend concentration and NaHCO3 concentration of 1.6 g L−1, independent of the medium renewal rate.